Trade Unions and Transition – an Unfinished Story - Stojiljković, Zoran B. (Sociološki pregled, 2019)
In this paper, I begin with a broader understanding of transition as a process of moving from the national capitalism of the welfare state to globalized, disorganized, corporate capitalism, within which the transition of post-communist societies is an important sequence that gives the process a planetary character (Vuletić, 2012). Structurally, the paper consists of three narrow thematic units within which I seek to adequately apply the three complementary methodological approaches. The first part is devoted to the global framework of change and is dominated by a system approach in which the crisis is considered through changes in the external framework and non-corresponding changes in the structure and functions of trade unions. Then, there is a discussion of transitional Serbia and the position of trade unions and the employees, in which I rely on an institutional approach, first of all, to analyze the transformed economic, work and social framework. The third part is devoted to the areas, opportunities and actors of change and the ideational approach appropriate for them, related to values - the vision and mission of unions, first and foremost. In methodical terms, the analysis of the Serbian transition and its peculiarities is a special case study within which, given the author’s decades of research and practical involvement in trade unions, an action research is conducted, as one might call it, or a kind of participatory observation. The key thesis I am trying to argue is that employees and unions are one of the biggest transitional losers and that growing inequalities and power imbalances will not change without a thorough revision of the dominant neo-liberal pattern by which globalization processes take place.